Strategi Penguatan Halal Supply Chain Di Indonesia Dalam Menghadapi Global Islamic Economy - Aslikhah Aslikhah; Alimatul Faridah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Muslim and non-Muslim communities in several countries in the world have taken great opportunities in the halal industry. Countries with a majority Muslim population compete with each other to become the world's halal supply chain. The purpose of writing this article is to find out 1) the KNKS strategy on strengthening the halal supply chain for halal products in Indonesia 2) The strategy of the Ministry of National Development Planning in accelerating the halal supply chain of the halal industry in Indonesia 3) To determine economic conditions of Indonesia in the global Islamic Economy. This article uses secondary data obtained through reports on the GIE 2020/2021 Report, KNKS, and the Ministry of National Development Planning. Data analysis in this article uses four stages, namely data reduction, data categorization, then data verification, and finally with data display. Conclusions are drawn by describing the report in the tables. It can be concluded that, with a large population and a Muslim majority as a destination country for investment in halal products, the strategies undertaken by stakeholders are directed at strengthening Indonesia's halal supply chain towards the world's halal axis.